2021
DOI: 10.1038/s41598-021-85789-z
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation to continuous mowing makes the noxious weed Solanum elaeagnifolium a superweed candidate by improving fitness and defense traits

Abstract: The role of disturbance in accelerating weed growth is well understood. While most studies have focused on soil mediated disturbance, mowing can also impact weed traits. Using silverleaf nightshade (Solanum elaeagnifolium), a noxious and invasive weed, through a series of field, laboratory, and greenhouse experiments, we asked whether continuous mowing influences growth and plant defense traits, expressed via different avenues, and whether they cascade into offspring. We found that mowed plants produced signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 92 publications
2
35
0
Order By: Relevance
“…The images for trichome count were consistently captured at 60× magnification which contains ~5.32 mm 2 leaf area measured using ‘Nanoeye’ software linked to DSEM. We calculated the trichome density 1 mm 2 as follows ( Chavana et al 2021 ; Watts and Kariyat 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…The images for trichome count were consistently captured at 60× magnification which contains ~5.32 mm 2 leaf area measured using ‘Nanoeye’ software linked to DSEM. We calculated the trichome density 1 mm 2 as follows ( Chavana et al 2021 ; Watts and Kariyat 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a comparison of S. elaeagnifolium populations within and beyond their ancestral range, Petanidou et al (2018) found variations in resource allocation patterns that directly affect the pollinator visitation rate and fruit set [28]. Moreover, being self-incompatible and having nectar-less flowers, understanding the intricate details of the pollination biology of such weed species is important, as their reproduction ability, and hence propagule supply, plays a critical role in their uncontrollable spread and establishment [30]. To examine this, we documented the pollination biology of S. elaeagnifolium in the LRGV by identifying the major buzz pollinators, their buzzing acoustic parameters (buzzing frequency, amplitude, duration of buzzing), as well estimating the effects of frequency and duration of buzzing on pollen extraction.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that buzz pollinators will vary in their buzzing properties (frequency, amplitude) during S. elaeagnifolium pollination and consequently aid in seed set. Apart from threatening the pollination success of other native plants [26,30], S. elaeagnifolium also serves as a reservoir host for 'Candidatus Liberibacter solanacearum' which causes Zebra Chip disease of the potato [31]. Understanding the role of S. elaeagnifolium pollinators and studying the effects of buzz pollination traits such as buzzing frequency on S. elaeagnifolium reproductive success in the native range will provide us better knowledge of how pollination traits affect the invasiveness of the species.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies have focused on soil‐mediated disturbance, mowing can also impact weed traits. Mowed plants produce significantly a smaller number of fruits, and a smaller number of total seeds per plant, but have higher seed mass, and germinate more and faster (Chavana et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mowed plants produce significantly a smaller number of fruits, and a smaller number of total seeds per plant, but have higher seed mass, and germinate more and faster (Chavana et al, 2021).…”
mentioning
confidence: 99%